Cases of Child Abuse by Parents: An Analysis of Islamic Law on Children's Rights - Intan Nurmajidah; Zahwa Dinaya Zulharman; Adek Suryani; Indra Aziz; Raja Muda Pahlevi (ISNU Sumatera Utara, 2025)
Violence against children by parents is an increasingly worrying phenomenon in modern life. From an Islamic legal perspective, children have a number of fundamental rights that must be fulfilled, such as the right to protection, education, affection, and safety. This article aims to analyze the forms of violence against children in the family and examine how Islamic law regulates and protects children's rights based on the principles of maqasid sharia. The method used is a qualitative approach with a literature review of verses of the Quran, hadith, and fiqh literature. The results of the study indicate that Islam highly values ​​the protection of children and considers violence by parents a serious violation of parental trust and responsibility. This study recommends the importance of family education and the application of sharia values ​​in child-rearing patterns.